2015
DOI: 10.1161/circinterventions.114.001779
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Clinical Outcomes of Transcatheter Heart Valve Thrombosis

Abstract: Background— Valve thrombosis has yet to be fully evaluated after transcatheter aortic valve implantation. This study aimed to report the prevalence, timing, and treatment of transcatheter heart valve (THV) thrombosis. Methods and Results— THV thrombosis was defined as follows (1) THV dysfunction secondary to thrombosis diagnosed based on response to anticoagulation therapy, imaging modality or histopathology findings, or (2) mobile mass detected on THV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
166
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 260 publications
(174 citation statements)
references
References 31 publications
4
166
1
3
Order By: Relevance
“…In the relatively young era of percutaneous aortic valve replacement, an increasing number of reports has emerged describing cases of clinically relevant subacute post-TAVR valve thrombosis and recently identified reduced leaflet motion in MDCT, which may correspond to a subclinical surrogate of valve thrombosis [10,11,[23][24][25]. These reports about post-TAVR valve thrombosis and hindered leaflet function have generated debate about the clinical relevance of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the relatively young era of percutaneous aortic valve replacement, an increasing number of reports has emerged describing cases of clinically relevant subacute post-TAVR valve thrombosis and recently identified reduced leaflet motion in MDCT, which may correspond to a subclinical surrogate of valve thrombosis [10,11,[23][24][25]. These reports about post-TAVR valve thrombosis and hindered leaflet function have generated debate about the clinical relevance of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the appropriate anticoagulation strategy after TAVR remains an important clinical challenge that has resulted in a large variability of antithrombotic therapies, ranging from triple therapy (DAPT + oral anticoagulation [OAC]) to vitamin-K antagonists (VKA) alone [9]. Finally, recent reports on low but clinically relevant incidence of valve thrombosis hindering prosthesis function may further lead to an upheaval in the landscape of thrombotic therapy after TAVR [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Latib et al first reported the frequency, clinical presentation and management of THV thrombosis from a multicenter registry [13]. The overall incidence of symptomatic THV thrombosis was 0.6%.…”
Section: Clinical and Subclinical Thv Thrombosismentioning
confidence: 99%
“…THV thrombosis presented as thickened leaflets or thrombotic apposition of leaflets in 76.9% and thrombotic mass on the leaflets in 23.1%. 23 out of 26 patients (88.4%) were successfully treated with anticoagulation; two patients underwent a transcatheter valve-in-valve procedure and one patient underwent surgical aortic valve replacement [13]. More recently, hypoattenuated leaflet thickening (HALT) and reduced leaflet motion (RELM) of bioprosthetic aortic valves associated with normal transvalvular gradients (possibly related to subclinical leaflet thrombosis) have been reported as affecting both transcatheter and surgical aortic valves.…”
Section: Clinical and Subclinical Thv Thrombosismentioning
confidence: 99%
“…The largest cohort of patients with transcatheter heart valve (THV) changes was published by the Milan group, who presented multicenter data on 4266 patients undergoing TAVI [19]. The authors defined THV dysfunction as a mean gradient of 20 mmHg on echocardiography, and THV thrombosis when according changes visualized in echo, CT, or histopathology.…”
mentioning
confidence: 99%